FAKTOR-FAKTOR PENERIMAAN INDIVIDU DALAM IMPLEMENTASI TI DI PEMERINTAH KOTA BOGOR - Layungsari Layungsari; Putu Wuri Handayani; Yova Ruldeviyani (Jurnal Sistem Informasi, 2015)
The use of Information Technology (IT) in public sector organizations cannot always be applied properly. This could lead to failure of Information Systems. Many literature states that successful implementation of an information system is very dependent on the acceptance level of the system by its users. The Government of Bogor City as a public sector organization in Indonesia has been active in the development of IT. From 2008 to 2013, the Government of Bogor City developed nine application, four of which has running with low utilization and the other five applications no longer operate as a result of very minimum user. This study analyzes the individual factors that influence the acceptance of implementation of IT in the Government Environment using TAM. This is quantitative Survey Research using sample of 410 employees of Bogor city. Data processing was performed using descriptive statistical techniques and PLS-SEM. The results prove that the Perceived Usefulness and Perceived Ease of Use has a significant influence on the Behavioral Intention to use IT at Government of Bogor City. Behavioral Intention has a significant influence on the Actual IT Use and Perceived Ease Perceived Ease of Use had a significant effect on the Perceived Usefulness.